Availability of Cedrus atlantica annual rings in monitoring the change in airborne sulfur pollution - SEVIK, Hakan; OZEL, Halil Baris; OZDEMIR, Mehmet (GSC Online Press, 2023)
Heavy metals are one of the components that threaten human health and the ecosystem the most among the components of air pollution, which has become a global problem. Sulfur, an important air pollutant, is not only a serious threat to human health at high concentrations, but also extremely dangerous for the ecosystem and constitutes a significant part of the pollutant load in many cities. Therefore, monitoring the change of sulfur pollution in the air is very important. In this study, the usability of Cedrus atlantica annual rings was investigated in observing the change in sulfur pollution in the air. Within the scope of the study, samples taken from a Cedrus atlantica tree grown in Düzce, one of Europe's 5 most polluted cities, were analyzed, and the change of sulfur concentration from the past to the present was investigated. As a result of the study, the highest concentrations were obtained in the outer bark and north direction. In addition, it has been found that there has been a substantial increase in sulfur pollution in recent years.
Keywords: Heavy metal; Biomonitor; Cedrus atlantica; Annual ring; Sulfur; 13. Climate action; 11. Sustainability; 15. Life on land; 3. Good health